In vitro antimicrobial efficiency of a mouthwash containing triclosan/gantrez and sodium bicarbonate - Pires, Juliana Rico [UNESP]; Rossa Júnior, Carlos [UNESP]; Pizzolitto, Antonio Carlos [UNESP] (FapUNIFESP (SciELO), 2007)
Several antiseptic substances have been used as adjuncts to routine mechanical procedures of oral hygiene, based on their antimicrobial effects. The objective of this study was to assess in vitro the antimicrobial efficiency of 2 mouthwash containing Triclosan/Gantrez and sodium bicarbonate in comparison to both positive and negative controls. Standard strain samples of Escherichia coli, Pseudomonas aeruginosa, Actinomyces viscosus and Bacillus subtilis were used. Samples of Streptococcus mutans and Gram-negative bacilli were collected from 20 volunteers (10 with a clinically healthy periodontium and 10 presenting biofilm-associated gingivitis). Evaluation of the antimicrobial activity was performed by determining the minimal inhibitory concentration (MIC). The results indicated that the test solution inhibited the growth of both Gram-negative and Gram-positive microorganisms from the volunteers' saliva as well as that of the standard strains at the MIC dilution of 1:20, whereas the MIC dilution of 0.12% chlorhexidine against the same bacteria was 1:80. Thus, even though the tested mouthrinse solution presented an in-vitro antimicrobial activity superior to that of a placebo, it was inferior to that of chlorhexidine.
Keywords: Anti-bacterial agents; In vitro; Triclosan; bicarbonate; chlorhexidine; maleic acid derivative; placebo; polyvinyl derivative; polyvinylmethoxyethylene maleic anhydride copolymer; polyvinylmethoxyethylene-maleic anhydride copolymer; tissue adhesive; topical antiinfective agent; triclosan; unclassified drug; adult; drug effect; female; Gram negative bacterium; Gram positive bacterium; human; male; mouthwash; Adult; Anti-Infective Agents, Local; Chlorhexidine; Female; Gram-Negative Bacteria; Gram-Positive Bacteria; Humans; Male; Maleates; Mouthwashes; Placebos; Polyvinyls; Sodium Bicarbonate; Tissue Adhesives